COMMUNITY PERCEPTION TOWARD THE QUALITY OF PUBLIC SERVICES IN LICENSING SERVICES ON THE OFFICE OF INVESTMENT AND INTEGRATED LICENSING SERVICES OF SLEMAN REGENCY - Rahma Ardi Kurniawan; Widhihatmini Widhihatmini (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2019)
This research is motivated by the existence of public complaints about the quality of services in the Office of Investment and Integrated Licensing Services (DPMPPT) of Sleman Regency including slow permit processes, limited human resource competence, and expensive permitmanagement fees. The purpose of this study is to determine public perceptions of the quality of public services in DPMPPT Sleman Regency licensing services. This research used descriptive quantitative method. The data were collected through questionnaire, interview, and documentation. The conclusion of this research is that community perception toward quality service at the Office of Investment and Integrated Licensing Service of Sleman Regency can be categorized as excellence in terms of complaint and suggestion handling. The quality of service that is categorized as good are requirement, system, mechanism, and procedure, fee, specification product of services, officer competence, officer attitude, and facility and infrastructure. Moreover, the quality of completion time is categorized as not good.